Effect of Active - Resisted Exercise and Stretching on Pronated Foot Posture in Female Indian Classical Kathak Dancer (International Journal of Physiotherapy, 2025)
Background: Kathak, a classical Indian dance form, involves intricate footwork and expressive movements that often result in a pronated foot posture among female dancers. This study investigates the effectiveness of exercise interventions in correcting pronated foot posture in Kathak dancers.Methods: Sixty female Kathak dancers were divided into two groups: one group participated in both exercise and dance, while the other group engaged in dance only. Foot posture, arch index, and range of motion were evaluated using the Foot Posture Index (FPI), Arch Index (AI), and universal goniometer measurements before and after a 6-week intervention period. Statistical analysis was performed using SPSS.Results: In Group A, significant improvements were observed in FPI scores for both right (p